Simulation model of ANN and PID controller for direct current servo motor by using Matlab/Simulink - Hashmia S. Dakheel; Zainab B. Abdullah; Najat Shyaa Jasim; Salam Waley Shneen (Universitas Ahmad Dahlan, 2022)
In the current era, researchers have been active in confirming and achieving their work through simulation using the computer program Matlab, in addition to the comparison between different control methods is also one of the prevailing behaviors, and the focus has been on the use of electrical machines in industry through multiple applications. Researchers in this study selected type of electric motors and two types of control systems for comparison, and to verify the possibility of improving the system’s work performance through the simulation results, the process of achieving the objectives of the current research is carried out. This paper presents using conventional proportional-integral-derivative (PID) controller and artificial neural networks (ANN) with direct current servo motor (DCSM) in order to obtain good performance characteristics because of efficient and widely use of this motor in the fields of control. The motor model in addition to the controller is built using Matlab simulation software. A comparison was made between these controllers (PID and ANN), where the simulation results indicate that the neural networks being developmental in the process of simulating the operation of the servo motor type and got good performance and better results from the traditional real-time console use case.